Formation and Properties of Mixed Ferritic–Martensitic Microstructures in the Air‐Hardening Steel LH800. Issue 9 (27th February 2014) - Grydin, Olexandr; Nuernberger, Florian; Zou, Ying; Schaper, Mirko; Brosius, Alexander; Kawalla, Rudolf
<x xml:space="preserve">Abstract</x> Processing of thin metal sheets of air‐hardening steels differs from the usual processing and includes deep drawing in the ferritic condition, a cutting operation and a thermal treatment of austenitizing, air quenching and an optional tempering, respectively. The mechanical properties of the low carbon steel LH800 increase due to air‐hardening, e.g., the tensile strength rises from about 480 MPa in the as‐delivered ferritic condition up to more than 1000 MPa in the martensitic condition. The experimental work aims to create a dual phase microstructure consisting of martensite and ferrite by austenitizing below the Ac3 temperature and to characterize the mechanical properties. Based on the experimental data mechanical properties and microstructural parameters could be correlated. For example, the tensile strength can be calculated using the rule of mixture for the microstructure fractions of martensite and ferrite. The yield stress can be predicted by extending the rule of mixture regarding the Hall–Petch equation. As the results reveal the mechanical properties can be controlled very well regarding tensile strength and yield stress by austenitizing at comparatively low temperatures.